Speak, memory an autobiography revisited - Nabokov, Vladimir Vladimirovich 1899-1977 (Vintage international, 1989)
This book, first published in 1951 as Conclusive evidence and then assiduously revised in 1966, examines Nabokov's life and times while offering incisive insights into his major works, including Lolita, Pnin, Despair, The gift, The real life of Sebastian Knight, and The defense.